Effect of nicotine on dual‐species biofilms of Streptococcus mutans and Streptococcus sanguinis. Issue 2 (19th November 2013) - Li, Mingyun; Huang, Ruijie; Zhou, Xuedong; Zhang, Keke; Zheng, Xin; Gregory, Richard L.
Abstract Both Streptococcus mutans and Streptococcus sanguinis are normal bacterial inhabitants of dental plaque. Streptococcus mutans is the major agent causing dental caries. It has been well documented that nicotine affects the growth of S. mutans. This study investigated the effect of nicotine on mono‐ and dual‐species growth of S. mutans and S. sanguinis. The results indicate that nicotine has no significant effect on S. sanguinis grown in either mono‐ or dual‐species biofilms. However, nicotine significantly increased (P < 0.05) the growth of S. mutans in dual‐species biofilm formation. In addition, the CFU level of S. sanguinis was higher than S. mutans without nicotine in the culture. With the addition of nicotine, the level of S. mutans biofilm was significantly enhanced as the nicotine concentration increased over the level of S. sanguinis in dual‐species biofilm, and we also got the same result from the fluorescence in situ hybridization detecting the two bacteria grown in biofilm formation. The exopolysaccharide (EPS) of S. mutans has also been increased by the increasing nicotine concentration, while the EPS of S. sanguinis was decreased or inhibited by the affected nicotine. The data further confirm that nicotine is able to enhance the growth of S. mutans.